CREATING PATTERNS USING VARIOUS MATERIALS AND TOOLS IN VISUAL ARTS EDUCATION - Karimova Shamsiyabonu Toxir qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article explores methods for creating ornamental patterns using diverse materials and tools in visual arts education. Emphasis is placed on how the use of multiple media, including traditional and modern tools, enhances students’ creativity, technical skills, and aesthetic perception. The study discusses the benefits of experimentation with different textures, surfaces, and materials in developing artistic competence. Practical examples illustrate how hands-on activities and guided exercises foster students’ engagement, problem-solving abilities, and innovative thinking.